AsnB Mediates Amidation of Meso-Diaminopimelic Acid Residues in the Peptidoglycan of Listeria monocytogenes and Affects Bacterial Surface Properties and Host Cell Invasion - Sun, Lei; Rogiers, Gil; Courtin, Pascal; Chapot-Chartier, Marie-Pierre; Bierne, Hélène; Michiels, Chris W. (Frontiers in Microbiology, 2021)
A mutant of Listeria monocytogenes ScottA with a transposon in the 5’ untranslated region of the asnB gene was identified to be hypersensitive to the antimicrobial t-cinnamaldehyde. Here, we report the functional characterization of AsnB in peptidoglycan modification and intracellular infection. While AsnB of Listeria is annotated as a glutamine-dependent asparagine synthase, sequence alignment showed that this protein is closely related to a subset of homologues that catalyze the amidation of meso-diaminopimelic acid (mDAP) residues in the peptidoglycan of other bacterial species. Structural analysis of peptidoglycan from an asnB mutant, compared to that of isogenic wild-type and complemented mutant strains, confirmed that AsnB mediates mDAP amidation in L. monocytogenes. Deficiency in mDAP amidation caused several peptidoglycan- and cell surface-related phenotypes in the asnB mutant, including formation of shorter but thicker cells, susceptibility to lysozyme, loss of flagellation and motility, and a strong reduction in biofilm formation. In addition, the mutant showed reduced invasion of human epithelial JEG-3 and Caco-2 cells. Analysis by immunofluorescence microscopy revealed that asnB inactivation abrogated the proper display at the listerial surface of the invasion protein InlA, which normally gets cross-linked to mDAP via its LPXTG motif. Together, this work shows that AsnB of L. monocytogenes, like several of its homologs in related Gram-positive bacteria, mediates the amidation of mDAP residues in the peptidoglycan and, in this way, affects several cell wall and cell surface related properties. It also for the first time implicates the amidation of peptidoglycan mDAP residues in cell wall anchoring of InlA and in bacterial virulence.